Bahasa Inggris - Hariyadi Sabar; Cipta Althaf Ronaza; Myranda Zahrah Putri (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
A legal identity document is the right of every citizen because it is a prerequisite in accessing public services. This study aims to assess the implementation of Presidential Regulation Number 62 of 2019 on the National Strategy of Strengthening Civil Registration and Vital Statistics (Stranas Percepatan AKPSH), which focuses on regulatory synchronization and services at a local level. A qualitative analysis approach was used, consisting of a literature study and in-depth interview methods. The research sample includes ministries/agencies at the central level, also several local governments, i.e., Palu City, Bantul Regency, Muaro Jambi Regency, East Sumba Regency, DKI Jakarta Province, and Surabaya City. The study shows that the central government has made policies to facilitate vulnerable groups in CRVS access. Local governments have policies that make it easier for vulnerable groups to get CRVS access; innovate administrative services; carry out socialization, advocacy, and education efforts involving third parties; and increase cooperation between regional government organizations (OPD) in implementing integrated civil registration services. However, there are still vulnerable groups that are not accommodated. Implementation at the regional level still has infrastructure readiness, human resources, and required special data collection team availability. Therefore, the determination of the vulnerability category becomes essential. This study recommends that it is necessary to create an additional classification of vulnerable groups in CRVS. In addition, it is essential to strengthening outreach to vulnerable groups in CRVS, especially at the regional level.